Overcoming the tension between Wisdom, Philisophy and Rhetoric in Quintilian and Saint Augustine - Correa, Andrés Covarrubias (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
In this article, I intend to show that Quintilian idea of philosophy as one that has adopted the knowledge of rhetoric is confirmed by the necessity, known above all in the Stoicism, of reinstating a truly persuasive speech, leaving a flat and dull language, to accomplish the task of giving to the city the best and excellent ideas. To do so there is need to prove, to delight the audience and to move the affections. In this way, Quintilian reveals that Stoic philosophy is a profound knowledge and an exemplary ethical matrix claiming a vivid, persuasive and brilliant language to offer its most dignified expression. Saint Augustine, who is educated in the Roman rhetorical tradition, assumes some elements given by Quintilian, but at the same time he shows that both philosophy and rhetoric should find their final orientation from the Holly Scriptures.
Keywords: Rhetoric; Quintilian; Stoics; Saint Augustine; Platonism